2010
DOI: 10.3109/08860221003611752
|View full text |Cite
|
Sign up to set email alerts
|

Thiopental improves renal ischemia–reperfusion injury

Abstract: Thiopental and propofol, especially thiopental, are more effective to protect renal I/R injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 30 publications
2
23
0
Order By: Relevance
“…Contrary to this Doğan et al [17] reported that thiopental has beter antioxidant effects than propofol according to their comparative study.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…Contrary to this Doğan et al [17] reported that thiopental has beter antioxidant effects than propofol according to their comparative study.…”
Section: Discussionmentioning
confidence: 79%
“…Prophylactic antiapoptotic treatment can be an effective therapeutic strategy for the prevention of I/R injury [22] . Thiopental is a highly lipid-soluble anesthetic, which has indicated antioxidant effect by inhibiting lipid peroxidation in ischemia/reperfusion injury [17] . Protective effects of thiopental for renal ischemia/reperfusion injury was searched in several and compared with the other intravenous agents [13,17,23] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, approaches to lessen I/R injury have been extensively studied, and administration of pharmacologic agents such as anesthetics have been shown to be protective against renal I/R injury 2,3 . Dexmedetomidine, a commonly used anesthetic, could exert renoprotective effects on normoglycemic animals when administered before renal I/R [4][5][6] .…”
Section: Introductionmentioning
confidence: 99%